Consequences of Distributive Justice Climate Based on Target Similarity Approach: Hierarchical Linear Model Analysis - Ratno Purnomo; Siti Zulaikha Wulandari; Retno Kurniasih (Universitas Hayam Wuruk Perbanas, 2022)
Research on the consequences of organizational justice climate will still grow in the future, especially its cross-level impact on individual outcomes. This study examines the unique combined impact of a multi-foci distributive justice climate on trust in supervisors, organizational commitment, and proactive behavior. In estimating our proposed model, we involved 153 workforces of public sector organizations in Banyumas, Central Java, and analyzed them using Hierarchical Linear Modeling (HLM). This study confirmed that multi-foci and target-based distributive justice climate consequences are supported. Distributive justice climate foci organization positively impacts organizational commitment, while the distributive justice climate foci supervisors positively impact trust in supervisors. In addition, the distributive justice climate also impacts proactive behavior. Trust in supervisors, and organizational commitment are proven to mediate the relationship between a distributive justice climate and proactive behavior. This research offers unique practical and theoretical contributions to the public sector industry. Our work is the first research using a multi-foci and target similarity model and related literature by applying Social Exchange Theory (SET) to the constructs of a multi-foci distributive justice climate, trust in supervisors, organizational commitment, and proactive behavior.